Janus Surface Micelles on Silica Particles: Synthesis and Application in Enzyme Immobilization. Issue 4 (3rd December 2020) - Wang, Huan; Hou, Wangmeng; Liu, Yingze; Liu, Li; Zhao, Hanying
Abstract: In these years, synthesis and applications of Janus structures have aroused great interest for large‐scale applications in chemistry and materials science. Up to now, Janus particles with different morphologies and different functionalities have been synthesized in solutions, but the synthesis of Janus particles on solid surfaces has not been touched. In this research, Janus surface micelles (JSMs) are fabricated on the surfaces of silica particles by polymerization induced surface self‐assembly (PISSA) approach, and the JSMs are used for enzyme immobilization. Usually, enzyme immobilization should be able to optimize the performance of the immobilized enzymes, and an ideal immobilization system must offer protection to the immobilized enzyme with retained bioactivity. Herein, it is demonstrated that JSMs on silica particles can be used as an ideal platform for the immobilization of enzymes. To prepare JSMs, poly(2‐(dimethylamino) ethyl methacrylate) macro chain transfer agent (PDMAEMA‐CTA) brushes on silica particles and poly(di(ethylene glycol) methyl ether methacrylate) macro CTA (PDEGMA‐CTA) are employed in reversible addition‐fragmentation chain transfer dispersion polymerization of styrene. After polymerization, JSMs with polystyrene cores and PDMAEMA/PDEGMA patches on the surfaces are prepared on silica particles. After quaternization reaction, the quaternized PDMAEMA patches are used for the immobilization of enzymes. Experimental results turn out that enhanced bioactivities of the immobilized enzymes are achieved and the enzyme molecules are well protected by surface Janus structures. Abstract : Enzyme immobilization is able to optimize the performance of the immobilized enzymes. An ideal immobilization system must offer protection to the immobilized enzyme with retained bioactivity. In this research, Janus surface micelles (JSMs) are fabricated on the silica particles by polymerization induced surface self‐assembly process. It is demonstrated that JSMs can be used as an ideal platform for the immobilization of enzymes.